Religious Moderation: A Concept of Genealogy and Internalization in the Maqashid Sharia Classic - Muhammad Nurravi Alamsyah; Salma Azizah Wifqi; Zaini Fasya; Ahmad Nur Ismail (MultiTech Publisher, 2024)
Islamic law will inevitably take some forms. There is room for reformulation even when using different legal istinbat techniques. Maqashid sharia is among the issues that Islamic legal scholars are concerned with. Maqashid, as a historical field, has developed quickly, moving from being an integral science to an autonomous one. It is crucial that legal observers understand how intricate the maqashid development process is. In this instance, the author—who is regarded as the father of maqashid sharia—presents a study of the evolution of classical maqashid prior to Imam Syatibi. The problems are formulated as follows: 1) How does the concept of maqashid compare to four figures prior to Syatibi? and 2) How does maqashid fit into the concept of religious moderation in relation to four figures? A descriptive-analytical technique is employed in the qualitative research methodology. According to the study's findings, the ideas of Imam al-Juwaini, al-Ghazali, al-Qarafi, and al-Thufi are pertinent and consistent with the four key pillars of religious moderation—tolerance, acceptance of local customs, national commitment, and nonviolence. Thus, the idea of religious moderation aligns with the principles of maqashid sharia.